The Study of the Influence of the Ceiling Structure on Acoustics in Contemporary Churches - Anna SYGULSKA (Archives of Acoustics, 2019)
The paper discusses acoustic problems in the contemporary Catholic church, and presents a study of the influence of the ceiling structure on acoustics in the interior for two types of ceiling structures, i.e. the truss type and the reinforced concrete one. The investigations involved six contemporary churches: three buildings with a truss type ceiling and three buildings with a reinforced concrete ceiling. The results reveal that in churches with a truss type ceiling, acoustic parameters reach values close to recommendations. In contrast, churches with a concrete ceiling create very unfavourable acoustic conditions. The investigations rendered it possible to calculate the sound absorption coefficient α for the truss type cover.